Pengaruh Harga Dan Promosi Terhadap Kepuasan Pelanggan: Survey pada pelanggan perusahaan penyedia jasa Event Organizer di Kota Bandung - Iman Rohiman; Farid Riadi; Ujang Wawan Sam Adinata; Asep Rochyadi Suherman (Center of Research, STIE Pasundan, Bandung, Indonesia., 2022)
This study aims to determine the effect of price and promotion on customer satisfaction. The research object is customers who use the company's services at one of the event organizer service providers in Bandung City, with 45 customers as respondents. The authors use descriptive analysis techniques and verification analysis to determine the magnitude of the influence of price and promotion on customer satisfaction. The study results indicate that there is a significant effect of price and promotion on customer satisfaction. Furthermore, the study results indicate that to increase customer satisfaction; the company should provide more detailed information to customers so that it is easy to understand. The company must also evaluate the existing bureaucracy to avoid confusing customers too much.